Absorbed organic residues in a Late Bronze Age II clay coffin with anthropoid lid from Tel Shadud, Israel. (April 2017) - Namdar, Dvory; Shoval, Shlomo; Amrani, Alon; van den Brink, Edwin C.M.; Kirzner, Dan; Beeri, Ron
Abstract: During salvage excavations carried out in 2013 on behalf of the Israel Antiquities Authority, a seemingly isolated clay coffin with anthropoid lid was uncovered on the lower east slope of Tel Shadud in the Jezreel Valley (van den Brink et al., 2016). The coffin and associated funerary gifts bear strong resemblance to comparable specimens known foremost from Deir el-Balah in the Gaza strip and Bet She'an in the Jordan Valley. This new find should be placed within the context of the Egyptian New Kingdom colonization process of the region during the Late Bronze Age II and succeeding Iron Age I (van den Brink et al., In press). The coffin was systematically sampled for absorbed organic compounds along its profile. The results of the residue analysis reveals a particular burial aspect associated with pre-burial treatment of the coffin.